Peran Team Leader dalam Mengintegrasikan Teori Akuntansi untuk Meningkatkan Efisiensi Penjualan dan Sumber Daya (Perusahaan Dancow Fortigrow Surabaya) - Sa'diyah, Aminatus; Hamid, Abdul (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
In a competitive business environment, operational efficiency is the key to company success. This research discusses the important role of a team leader at Dancow Fortigrow in integrating accounting theory to increase sales efficiency and resource management. Team leaders in this company are not only responsible for overseeing the sales and distribution team, but also utilize accounting principles to manage budgets appropriately, control costs, and determine competitive selling prices. They also use financial data to conduct sales performance analysis, optimize the use of company assets, and manage inventory effectively. Modern technology, such as ERP systems, supports their efforts in monitoring operational performance in real-time and making more informed decisions. This type of research uses the literature study method. The results of this research explain that the integration of accounting theory by team leaders not only strengthens the company's operational efficiency, but also increases its competitiveness in a competitive market. Keywords: Accounting Theory, ERP System, Resource Management, Sales Efficiency, Team Leader.